LEGAL REGULATION OF CRIMINAL LIABILITY OF THE EMPLOYER FOR NON-PAYMENT OF WAGES - Egor V. Makarov; Luiza Dantesovna Habibova; Irek A. Bikkinin (Russian Studies in Law and Politics)
In the presented work, a special problem of responsibility for the violation of one of the parties to the employment relationship, namely by the employer, of its obligations is considered: the issue of non-payment of wages by the employer to the employee and its regulation by law enforcement legislation. The authors set a goal to get a general idea of the adjacent border between labor and criminal law on the subject of violation of the employee’s right to remuneration for the work he has invested. Wages are the subject of labor relations, which are regulated by the branch of labor law. A person guilty of violating labor legislation is brought to disciplinary, material, civil, administrative and criminal liability. It is here that the bridge we need is located, connecting labor law itself and other areas of law. The authors draw their conclusions based on the analysis of the system of public law norms of the designated branches of legislation and the practice of their application.